Recognition and Enforcement of Foreign Judgments Lacking Reasons under Turkish Law - Hatice Selin Pürselim Arning; Can Yöney (Public and Private International Law Bulletin)
Under Turkish law, incorporation of reasoning in judgments is a matter directly stipulated in the Constitution and is deemed indispensable. However, the summary proceedings available in certain legal systems make it possible for courts to decide a case without conducting a complete examination of the dispute on its merits and without providing its underlying reasoning for its decision. Turkish courts may from time to time have to deal with requests for recognition or enforcement of judgments arising out of such proceedings. The approach the enforcing Turkish court should follow in such a case has constituted a serious issue for debate for a considerable period. The Court of Cassation Decision on the Unification of Judgments in 2012 also failed to resolve these discussions. In this study, we will first try to examine the importance reasoning has in Turkish civil law as well as the decisions of both the European Court of Human Rights and the Court of Cassation regarding the recognition and enforcement of foreign judgments lacking reasoning. Afterwards, we will explain our opinion on the matter, that it would be incorrect to follow a categorical approach; and rather that it would be more appropriate to examine the issue on a case-by-case basis.